Microelectronics‐Free, Augmented Telemetry from Body‐Worn Passive Wireless Sensors. Issue 4 (3rd March 2021) - Hajiaghajani, Amirhossein; Tseng, Peter
Abstract: Wearable wireless passive sensors are powerful potential building blocks of modern body area networks. However, these sensors are often hampered by numerous issues including restrictive read‐out distances due to near‐field coupling, fundamental tradeoffs in size/spectral performance, and unreliable sensor tracking during activity. Here, to overcome such issues implementing wearable sensing systems exhibiting coupled magnetic resonances are demonstrated. This approach is utilized to augment wireless telemetry from fully wearable, passive (zero electronics) resonator chains. Secondary receiver coils are integrated into fabric or skin to facilitate augmented read‐out from epidermal sweat, moisture, or pressure sensors—herein exhibiting enhanced read‐out range, relaxed constraints in sensor size (sensor spectral response becomes untethered from size) and reader‐sensor orientation. Unlike existing schemes, this readout method enables decoupled co‐readout of the sensor's distance and status, employed here for co‐measurement with human respiration. This type of decoupled readout can help compensate for movements that are so common in wearable monitoring. Simple to implement and requiring no microelectronics, this scheme streamlines into existing, body‐worn passive wireless telemetric systems with minimal modification. Abstract : Several drawbacks of passive wireless epidermal/implanted sensors such as short‐range, misalignment sensitivity, and large resonance frequency can be augmented by streamlining additional coupled resonators incorporated with clothes. This offers a greater level of misalignment tolerance and simultaneous multiparameter readout (sensor status plus the distance from the reader).